2002
DOI: 10.1046/j.1523-536x.2002.00187.x
|View full text |Cite
|
Sign up to set email alerts
|

Both Empowered and Powerless: Mothers’ Experiences of Professional Care When Their Newborn Dies

Abstract: Both empowered and powerless: mothers' experiences of professional care when their newborn dies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 18 publications
2
59
0
3
Order By: Relevance
“…Interviews with parents have demonstrated that health care providers can make families feel either supported or helpless after their infant or child dies. 2,[5][6][7] A fetal or infant death is a traumatic loss -often sudden and unexpected, sometimes forcing families to integrate the almost simultaneous experiences of birth and death. Intrusive thoughts and avoidant behaviors -once thought to be associated only with exposure to life-threatening traumas like war or assault -now are recognized as common symptoms in acute grief reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews with parents have demonstrated that health care providers can make families feel either supported or helpless after their infant or child dies. 2,[5][6][7] A fetal or infant death is a traumatic loss -often sudden and unexpected, sometimes forcing families to integrate the almost simultaneous experiences of birth and death. Intrusive thoughts and avoidant behaviors -once thought to be associated only with exposure to life-threatening traumas like war or assault -now are recognized as common symptoms in acute grief reactions.…”
Section: Introductionmentioning
confidence: 99%
“…10 Like for other trauma survivors, parents interviewed years and even decades after a child's death report a surprising level of detail regarding the event and can often retell the story of the loss, comments people made and upsetting aspects of their experience. 6,[11][12][13] During these high-stress times, seemingly benign mis-steps by a health care provider may be engrained in a bereaved parent's memory and replayed over and over in the years to come.…”
Section: Introductionmentioning
confidence: 99%
“…Patients' suffering from chronic illness as well as progressive malignant disease [7,9,24,32,40,71] and the next of kin's experiences have also been described in terms of powerlessness and helplessness. Such experiences have been illuminated in different groups of next of kin, for example parents having a disabled child [20], parents of stillborn children [41,49,64], informal caregivers of patients with chronic diseases [11] and cancer patients [18,46], and also within home care [11,79]. In fact, Ruppert stated that powerlessness is indeed one of the most frequently related psychological aspects related to the caregiving experience [61].…”
Section: Introductionmentioning
confidence: 99%
“…Parents report that they want information to be delivered in a comprehensible and consistent manner and they want to be included in the decision-making process and end-of-life care (Armentrout and Cates, 2011). Respect and responsiveness to the family's wellbeing, preferences, and cultural values is also imperative when delivering services under the family-centered model, as it provides an opportunity to develop a trusting and respectful relationship (Bruns and Steeples, 2001;Lundqvist et al, 2002).…”
Section: Principles Of Effective Communication In the Nicumentioning
confidence: 99%
“…Memories related to dissatisfaction with the care received have been found to remain for a lifetime (Laing and Freer, 2008;Lundqvist et al, 2002) and influence future relationships with health professionals (Bruns and Steeples, 2001). Giving parents limited information and choices, as well as communicating ineffectively, prevents parents from perceiving themselves as in control and involved in their infant's care, thereby furthering their distress levels (Armentrout and Cates, 2011), feelings of powerlessness (Lundqvist et al, 2002), and fear of not meeting their obligations as parents (Wocial, 2000).…”
Section: Principles Of Effective Communication In the Nicumentioning
confidence: 99%